1998
DOI: 10.1111/j.1600-079x.1998.tb00530.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐acetyl‐serotonin (normelatonin) and melatonin protect neurons against oxidative challenges and suppress the activity of the transcription factor NF‐κB

Abstract: It is now well established that the formation of free radicals and oxidative stress-induced neuronal cell death can be involved in various neurodegenerative disorders, including Alzheimer's disease and Parkinson's disease. The pineal hormone melatonin has been suggested to be a neuroprotective antioxidant. To better understand the molecular mechanism of this activity, we compared the ability of melatonin and its precursor, N-acetyl-serotonin (normelatonin), to protect human neuroblastoma SK-N-MC cells and prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 42 publications
2
63
0
1
Order By: Relevance
“…NF-kB activation is one of the most important redox-sensitive transcription factors and plays an essential role in gene expression of MnSOD [24]. Since MLT has been reported to regulate NF-kB activation [25], the role of these factors as mediators of MLT action on AOEs should therefore be investigated. An increase in mRNA levels may be due to an increase in the rate of transcription or an increase in mRNA half-life stability.…”
Section: Discussionmentioning
confidence: 99%
“…NF-kB activation is one of the most important redox-sensitive transcription factors and plays an essential role in gene expression of MnSOD [24]. Since MLT has been reported to regulate NF-kB activation [25], the role of these factors as mediators of MLT action on AOEs should therefore be investigated. An increase in mRNA levels may be due to an increase in the rate of transcription or an increase in mRNA half-life stability.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a-tocopherol treatment of humans in the DATATOP study for mitigation of Parkinson's disease (PD) revealed that even after many months of ingestion, levels of this vitamin were not equilibrated within the cerebrospinal fluid, and still rising (Vatassery et al, 1998). In addition, melatonin is potentially of specific value to the CNS where it is able to induce antioxidant genes (Kotler et al, 1998) and to attenuate the LPS (lipopolysaccharide)-induced inflammatory responses (Sewerynek et al, 1995;Lezoualch et al, 1998;Sharman et al, 2002a,b). Melatonin has also been reported to ameliorate indices of anxiety induced by LPS (Nava and Carta, 2001).…”
Section: Melatonin May Reduce Some Aspects Of Brain Agingmentioning
confidence: 99%
“…Thus, the inhibition of one of these transcription factors with selective inhibitors is not sufficient for managing the upregulation of these cytokines following exposure to radiation (Linard et al 2004). Melatonin has an inhibitory effect on the NF-κB gene expression in stress situations such as irradiation (Lezoualc'h et al 1998;Mohan et al 1995). Modulation of functional retinoidrelated orphan receptor-α (ROR-α) transcription factor is involved in this effect (García et al 2015).…”
Section: Effect Of Melatonin On Transcription Factors and Protein Kinmentioning
confidence: 99%